Proses pembuatan flywheel (roda gila) mesin Hammer Mill dengan metode Drilling, Milling, dan Turning di PT. Raja Ampat Indotim - Mulyana, Mulyana; Sumarjo, Jojo Sumarjo; Aripin, Aripin (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2024)
The research is aimed at the manufacture of flaywheel for hammer mill machines using the method of drilling, milling and turning, which aims to keep the engine rotation stable on the machine due to excess load and is a mass that rotates and is used as a storage of energy inside the machine. This research focuses on drilling, milling, and turning processes on low-carbon steels. (ST 40 Steel). The Flywheel is a component that is a plate that because of its weight can withstand drastic speed changes so that the rotation movement of the machinery shaft becomes more smooth. The drilling, milling and turning methods are machining methods that are widely used in the manufacturing industry. From the results of the research using the methods of drilling, milling and turning the following are on the process of making flywheel i.e. with the time of the drilling process of the production of sepie holes 62.82 minutes, the milling process of smoothing 2 surfaces of the work object 242.06 hours and the turning of the profile of 2 surface work object 117.6 hours with a total production time of about 15 days. Therefore, the results of this research provide useful guidance for the industry to optimize the drilling, milling and turning processes in flywheel manufacturing.